A Primer on Finance-Led Capitalism and Its Crisis - Robert Guttmann (Revue de la Régulation)
This contribution to the debate on finance-led capitalism seeks to identify the principal structural changes in the nature of finance over the last couple of decades. After analyzing the dynamic of financial innovation, emphasis is put on the process of securitization as the engine of a new form of financial capital, fictitious capital, which encourages asset bubbles. The burst of the latest bubble, centered on the U.S. housing market, has triggered the most serious financial crisis in decades and a serious global downturn. The article ends with a discussion of likely implications of this systemic crisis.